Kinetics of plasma triglycerides in abdominal obesity. Issue 1 (February 2017) - Björnson, Elias; Adiels, Martin; Taskinen, Marja-Riitta; Borén, Jan
Abstract : Purpose of review: Abdominal obesity is associated with a number of important metabolic abnormalities including liver steatosis, insulin resistance and an atherogenic lipoprotein profile (termed dyslipidemia). The purpose of this review is to highlight recent progress in understanding the pathogenesis of this dyslipidemia. Recent findings: Recent results from kinetic studies using stable isotopes indicate that the hypertriglyceridemia associated with abdominal obesity stems from dual mechanisms: (1) enhanced secretion of triglyceride-rich lipoproteins and (2) impaired clearance of these lipoproteins. The over-secretion of large triglyceride-rich VLDLs from the liver is linked to hepatic steatosis and increased visceral adiposity. The impaired clearance of triglyceride-rich lipoproteins is linked to increased levels of apolipoprotein C-III, a key regulator of triglyceride metabolism. Summary: Elucidation of the pathogenesis of the atherogenic dyslipidemia in abdominal obesity combined with the development of novel treatments based on apolipoprotein C-III may in the future lead to better prevention, diagnosis and treatment of the atherogenic dyslipidemia in abdominal obesity.